Relativistic Effects for Time‐Resolved Light Transport. (13th May 2015) - Jarabo, Adrian; Masia, Belen; Velten, Andreas; Barsi, Christopher; Raskar, Ramesh; Gutierrez, Diego
Abstract : We present a real‐time framework which allows interactive visualization of relativistic effects for time‐resolved light transport. We explore the effects of time dilation, light aberration, frequency shift and radiance accumulation by modifying existing models of these relativistic effects to take into account the time‐resolved nature of light propagation. We do not impose limiting constraints in the visualization, allowing the virtual camera to explore freely a reconstructed 3D scene depicting dynamic illumination. Moreover, we consider not only linear motion, but also acceleration and rotation of the camera. We further introduce a pinhole camera model into our relativistic rendering framework, and account for subsequent changes in focal length and field of view as the camera moves through the scene . Abstract: We present a real‐time framework which allows interactive visualization of relativistic effects for time‐resolved light transport. We leverage data from two different sources: real‐world data acquired with an effective exposure time of less than 2 picoseconds, using an ultra‐fast imaging technique termed femto‐photography, and a transient renderer based on ray‐tracing. We explore the effects of time dilation, light aberration, frequency shift and radiance accumulation by modifying existing models of these relativistic effects to take into account the time‐resolved nature of light propagation. Unlike previous works, we do not impose limiting constraints in the visualization, allowing the virtual camera to explore freely a reconstructed 3D scene depicting dynamic illumination. Moreover, we consider not only linear motion, but also acceleration and rotation of the camera. We further introduce, for the first time, a pinhole camera model into our relativistic rendering framework, and account for subsequent changes in focal length and field of view as the camera moves through the scene.